Hak Istri dan Kewajiban Suami Dalam Perspektif Hadis - Al Fannani, M. Zaini; Askar, Romlah Abu Bakar (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Rights and obligations are like two sides of the same coin. Its scope and function are also the same and evolving. When inequality occurs in rights more emphatically or broader than in duties, or vice versa, injustice will occur. Therefore rights and obligations going in balance tightly determine the viability and harmony of the relationship between the two. The success of marriage is not achieved unless both parties pay attention to their obligations, and the rights of the other party. In this writing will discuss the rights and obligations of husband and wife in the perspective of Hadith. The study used qualitative method with Library Research approach, focusing on collection, analysis and synthesis of data from various written sources such as hadith books reference books, scholarly articles and relevant digital sources. The results of the study show that husband and wife rights have been established in Islam. The right is aligned with the obligations of each party.